Playfulness: Sciences and Mathematics in Child Education (Research, Society and Development, 2022)
This study aims to analyze the use of Playfulness for teaching Science and Mathematics in Early Childhood Education. Pedagogical activities were developed to teach the concepts that involve science and mathematics in a class of Jardim I, in the municipality of Belém, State of Pará. The pedagogical intervention is considered to enhance the children's knowledge about science and mathematics, through games. A differentiated and positive restlessness was observed on the part of the children who participated in the activities considering their daily lives and experiences inside and outside the school. The entire school environment was used to carry out the activities. It was concluded that the work developed contributed significantly to the formation of children, stimulating a critical sense for the exercise of citizenship, considering, mainly, the current phase of human, cognitive and emotional development.